Role of adipocytokines in endometrial cancer progression - Li, Ran; Dong, Fang; Zhang, Ling; Ni, Xiuqin; Lin, Guozhi (Frontiers in Pharmacology, 2022)
Endometrial cancer is considered a significant barrier to increasing life expectancy and remains one of the most common malignant cancers among women in many countries worldwide. The increasing mortality rates are potentially proportional to the increasing obesity incidence. Adipose tissue secretes numerous adipocytokines, which may play important roles in endometrial cancer progression. In this scenario, we describe the role of adipocytokines in cell proliferation, cell invasion, cell adhesion, inflammation, angiogenesis and anti-apoptotic action. A better understanding of the mechanisms of these adipocytokines may open up new therapeutic avenues for women with endometrial cancer. In the future, larger prospective studies focusing on adipocytokines and specific inhibitors should be directed at preventing the rapidly increasing prevalence of gynaecological malignancies.